Nonclinical Toxicology and Toxicokinetic Profile of an Oral Lanthionine Synthetase C-Like 2 (LANCL2) Agonist, BT-11. (March 2019) - Leber, Andrew; Hontecillas, Raquel; Zoccoli-Rodriguez, Victoria; Ehrich, Marion; Davis, Jennifer; Chauhan, Jyoti; Bassaganya-Riera, Josep
BT-11 is an orally active, gut-restricted investigational therapeutic targeting the lanthionine synthetase C-like 2 pathway with lead indications in ulcerative colitis (UC) and Crohn disease (CD), 2 manifestations of inflammatory bowel disease (IBD). In 5 mouse models of IBD, BT-11 is effective at oral doses of 8 mg/kg. BT-11 was also efficacious at nanomolar concentrations in primary human samples from patients with UC and CD. BT-11 was tested under Good Laboratory Practice conditions in 90-day repeat-dose general toxicity studies in rats and dogs, toxicokinetics, respiratory, cardiovascular and central nervous system safety pharmacology, and genotoxicity studies. Oral BT-11 did not cause any clinical signs of toxicity, biochemical or hematological changes, or macroscopic or microscopic changes to organs in 90-day repeat-dose toxicity studies in rats and dogs at doses up to 1, 000 mg/kg/d. Oral BT-11 resulted in low systemic exposure in both rats (area under the curve exposure from t = 0 to t = 8 hours [AUC0-8 ] of 216 h × ng/mL) and dogs (650 h × ng/mL) and rapid clearance with an average half-life of 3 hours. BT-11 did not induce changes in respiratory function, electrocardiogram parameters, or behavior with single oral doses of 1, 000 mg/kg/d. There was no evidence of mutagenic or genotoxic potential for BT-11 up to tested limit doses using an Ames test, chromosomal aberration assay in human peripheral blood lymphocytes, or micronucleus assay in rats. Therefore, nonclinical studies show BT-11 to be a safe and well-tolerated oral therapeutic with potential as a potent immunometabolic therapy for UC and CD with no-observed adverse effect level >1, 000 mg/kg in in vivo studies.